2005
DOI: 10.1038/ni1254
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 17–producing CD4+ effector T cells develop via a lineage distinct from the T helper type 1 and 2 lineages

Abstract: CD4(+) T cells producing interleukin 17 (IL-17) are associated with autoimmunity, although the precise mechanisms that control their development are undefined. Here we present data that challenge the idea of a shared developmental pathway with T helper type 1 (T(H)1) or T(H)2 lineages and instead favor the idea of a distinct effector lineage we call 'T(H)-17'. The development of T(H)-17 cells from naive precursor cells was potently inhibited by interferon-gamma (IFN-gamma) and IL-4, whereas committed T(H)-17 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

104
3,284
15
68

Year Published

2007
2007
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 4,141 publications
(3,518 citation statements)
references
References 51 publications
104
3,284
15
68
Order By: Relevance
“…This corresponds to the Th1/Th2 paradigm proposed by Mosmann et al [1]. More recently, a third subset of Th cells, Th17 cells, has been described; this is a distinct lineage that does not share developmental pathways with either Th1 or Th2 cells [2,3]. Th17 cells are generally thought to be proinflammatory, especially through the production of IL-17 [2,3].…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…This corresponds to the Th1/Th2 paradigm proposed by Mosmann et al [1]. More recently, a third subset of Th cells, Th17 cells, has been described; this is a distinct lineage that does not share developmental pathways with either Th1 or Th2 cells [2,3]. Th17 cells are generally thought to be proinflammatory, especially through the production of IL-17 [2,3].…”
Section: Introductionmentioning
confidence: 67%
“…More recently, a third subset of Th cells, Th17 cells, has been described; this is a distinct lineage that does not share developmental pathways with either Th1 or Th2 cells [2,3]. Th17 cells are generally thought to be proinflammatory, especially through the production of IL-17 [2,3]. Th17 cells have been shown to participate in the development of autoimmunity, and also to play an important role in host defense against infection [4].…”
Section: Introductionmentioning
confidence: 99%
“…Th cells producing IL-17 (Th17 cells) are a distinct subset of effector cells that differentiate from naive T cells in response to IL-6 and TGF-b [25,26], whereas IL-23 serves as an important factor to expand previously differentiated Th17 cell populations and gd T cells [27,28]. Our data showed that C5a significantly increased IL-17 production by T lymphocytes in the presence of DC, while it had no influence on IL-17 production from T lymphocyte when DC were absent.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Th17 cells are described as a further specialized subset of CD4 1 effector cells in addition to the well-known Th1 and Th2 cells [1][2][3]. Upon stimulation Th17 cells acquire the capacity to produce the inflammatory cytokine IL-17 [4].…”
Section: Introductionmentioning
confidence: 99%